Examining the Degree of Conformity of media formats and artistic aspects of Roshd Nojavan Magazine with the Needs of Students - Shahmohammadi, Nayereh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: This research aimed to investigate the degree of adaptation of media formats and artistic aspects of Roshd Nojavan magazine to the media needs and interests of first-year high school students. Methods: This study is exploratory research in which a qualitative method (content analysis) and a survey (survey of students) were used. The sample in the qualitative part included nine issues of Roshd Nojavan Magazine published during the three years of 2020, 2021, and 2022, and the quantitative was 708 high school students. The research tools were content Checklist forms and semi-structured questionnaires. The reliability of the checklist forms and the questionnaire were 0.8 and 0.7 respectively. To analyze the data, coding of the texts with an inductive approach was used in the qualitative part, and descriptive statistics, one-sample chi-square test, and the Freidman test were used in the quantitative part. Results: In general, the results show that in terms of media formats, the magazine, in the formats of articles, entertainment, humor, and comic strips and headlines were completely in accord with the needs of students, in the formats of reports and notes, there was relative compliance, but in the format of interviews, the performance of the magazine was weak far from students’ expectation. Conclusion: From the artistic and aesthetic aspects of the magazine, the three indicators: letter size, the visualization of the magazine, and the color of the photos, do not fully comply with the needs and interests of the students, and adaptation of the students' need with the size of the photos is average.